Roger Bacon on substantial change - Trifogli, C (Routledge, 2021)
In the standard medieval interpretation of Aristotle’s theory of change, a substantial change occurs instantaneously. Roger Bacon rejects this standard reading and defends the alternative view that a substantial change is a temporal process, one that involves different stages occurring one after another. In this chapter, I present Bacon’s original view by analysing the extensive discussion he devotes to it in his late work Communia naturalium (Book I, part 4, distinction 1, chapters 1–3). The chapter is divided into four main parts. The first part gives an outline of Bacon’s account of the nature of substantial change as a change involving substances with different degrees of completion. The second part examines Bacon’s rejection of the common opinion that the time taken by a substantial change is due not to the substantial change itself but to an alteration concomitant with it. The third part presents Bacon’s arguments in favour of substantial degrees: that is, of intension and remission in substances. Bacon’s main argumentative line consists in showing that the existence of substantial degrees follows from the undisputed existence of accidental degrees. Bacon then defends his original view from some major Aristotelian auctoritates, which apparently deny the existence of degrees in substances. The fourth part deals with the major consequence of the existence of degrees of substances: that is, the temporality of substantial change. It focuses on Bacon’s concern to show that this consequence is not in contrast with the distinction between motion and mutation drawn by Aristotle in Physics V. In the conclusion I maintain that Bacon’s view about the existence of substantial degrees is not a version of the theory of plurality of substantial forms and that it is accidental degrees (intension and remission of qualities) rather than the plurality of substantial forms that provide the structural model for substantial degrees.